PENERAPAN FINGER HOLD THERAPY UNTUK MENURUNKAN TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI DI KP. SUKARAJA RT 02 RW 10 KELURAHAN BAROS WILAYAH KERJA PUSKESMAS CIGUGUR TENGAH KOTA CIMAHI TANGGAL 05 – 08 MEI 2025 - Setiawan, Guling; Tri Handayani, Aurum (Jurnal Kesehatan An-Nuur, 2026)
Hypertension is one of the chronic diseases that causes cognitive impairment and a decline in the quality of life for the elderly. Hypertension is a condition where blood pressure rises above normal values, with systolic blood pressure ≥140 mmHg and diastolic blood pressure ≥90 mmHg. The prevalence of hypertension increases every year, reaching 34.11% in Indonesia, with higher rates among women and in urban areas. The application of finger hold therapy is one of the complementary therapies that can be useful in lowering blood pressure in hypertensive clients, especially the elderly. Finger hold therapy is an alternative therapy that can stimulate the parasympathetic nervous system, thereby reducing blood pressure, heart rate, and respiratory rate. The method used in this case study is descriptive. This case study aims to describe nursing care for elderly families (≥60 years) with hypertension through the complementary therapy of finger hold therapy. The instruments used were a sphygmomanometer, standard operating procedure for finger hold therapy technique, and an observation sheet to determine the results before and after the intervention. The finger hold therapy technique was performed for 3 days for 30-60 minutes once in the morning. The case study results show that there was a decrease in blood pressure after the finger hold therapy technique was applied, in accordance with the target to be achieved. The evaluation obtained in this case study is that the nursing diagnosis of ineffective peripheral perfusion was resolved. It can be concluded that the finger hold therapy technique can be administered to elderly clients with hypertension because the finger hold therapy performed over 3 days was able to reduce the initial blood pressure from 160/100 mmHg to 140/90 mmHg. The author's suggestion to the client is to perform finger hold therapy as a complementary therapy to the core therapy with medication.